A Theoretical Framework for a Hybrid View of the N400 - Naumann, Ralf; Petersen, Wiebke (Frontiers in Psychology, 2021)
In this article we present a theoretical account of the N400 ERP component according to a hybrid view. In contrast to both the access and the integration view, hybrid views interpret this ERP component in terms of two cognitive operations: (i) (non-compositional) access of information, which is related to predictions (predictability component) and (ii) (compositional) integration of information which is related to plausibility (plausibility component), which follows the predictability component. Though there is empirical evidence for this view, what has been left open so far is how these two operations can be defined. In our approach both components are related to categorization. The critical word and the argument position it is related to are associated with categories that have a graded structure. This graded structure is defined in terms of weights both on attributes and values of features belonging to a category. The weights, in turn, are defined using probability distributions. The predictability component is defined in terms of the information gain w.r.t. non mismatched features between the two categories. The plausibility component is defined as the difference in degree of typicality between the two categories. Finally, the N400 amplitude is defined as a function of both components.